Analysis of the correspondence of the structural elements of AGU 75 variety harvest with the parameters of the winter oat idiotype model - M. V. Kuzenko (Новые технологии)
Currently, one of the tasks facing breeders is the creation of new varieties in terms of their economically important characteristics, close to the developed models of the «ideal variety». The main purpose of the research is a comparative analysis of economically important indicators of a new AGU 75 variety of wintering oat of the dual direction, and the compliance with the parameters of the idiotype for further use as a genetic source. The basis for this approach was the study of the variety in the nursery of competitive variety testing in the period of 2000–2015. The studies were carried out in the soil and climatic conditions of the southern foothill zone of the North-Western Caucasus according to the generally accepted methods and agrotechnics of cultivation. As part of our research we used long-term experimental data from field observations and records, laboratory studies, and the biochemical composition of grain. The article gives an assessment of the duration of the growing season, winter hardiness, yield, resistance to lodging and major diseases (crown and stem rust, septoria, head smut) of the AGU 75 variety in relation to the idiotype. A comparative analysis of the elements of the crop structure (productive tillering, panicle length, number of spikelets, number of grains, grain weight per panicle, grain weight per plant, weight of 1000 grains) of varieties and models was carried out. The content of fat and protein, as well as the filminess of the grain of the analyzed variety and ideal type, were determined. Based on the comparative analysis of economically useful traits of AGU 75 variety, the degree of their compliance with the previously developed optimal parameters of the wintering oat model variant was revealed. The expediency of using AGU 75 variety as a source of valuable traits in breeding work to increase winter hardiness, productivity, resistance to lodging and diseases, early maturity, shattering, filminess, as well as elements of the crop structure – productive tillering, grain weight per plant was experimentally confirmed.